Removal of Cu(II) from aqueous solutions using amine-doped polyacrylonitrile fibers - Aung, Kay Thwe; Hong, Seung Hee; Park, Seong Jik; Lee, Chang Gu (Applied Sciences (Switzerland), 2020)
Polyacrylonitrile (PAN) fibers were prepared via electrospinning and were modified with diethylenetriamine (DETA) to fabricate surface-modified PAN fibers. The surface-modified PAN fibers were used to evaluate their adsorption capacity for the removal of Cu(II) from aqueous solutions. Batch adsorption experiments were performed to examine the effects of the modification process, initial concentration, initial pH, and adsorbent dose on the adsorption of Cu(II). Kinetic analysis revealed that the experimental data fitted the pseudo-second-order kinetic model better than the pseudo-first-order model. Adsorption equilibrium studies were conducted using the Freundlich and Langmuir isotherm models, and the findings indicated that the PAN fibers modified with 85% DETA presented the highest adsorption capacity for Cu(II) of all analyzed samples. Moreover, the results revealed that the Freundlich model was more appropriate than the Langmuir one for describing the adsorption of Cu(II) onto the modified fibers at various initial Cu(II) concentrations. The maximum adsorption capacity was determined to be 87.77 mg/g at pH 4, and the percent removal of Cu(II) increased as the amount of adsorbent increased. Furthermore, the surface-modified PAN fibers could be easily regenerated using NaOH solution. Therefore, surface-modified PAN fibers could be used as adsorbents for the removal of Cu(II) from aqueous solutions.
Keywords: Adsorption models; Batch experiments; Cu(II) removal; Electrospun fibers; Polyacrylonitrile